An efficient and optimized protocol for tall fescue tissue culture and Agrobacterium-mediated genetic transformation - Hamid Reza Hosseini; Hassan Salehi; Morteza Khosh-Khui; Mehrangiz Chehrazi (Journal of the Saudi Society of Agricultural Sciences)
Festuca arundinacea Schreb. as an important turf widely exposed to biotic and abiotic stresses. Therefore, optimization of an efficient in vitro culture and transformation method to create optimal traits and tolerance against stresses as a major problem, is essential. In this research, in order to callus induction, embryos of ‘Barlexas II’, ‘Barvado’, ‘Coronado TDH’, and ‘Finelawn Elite’ cultivars were transferred on callogenesis medium containing 0–15 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) and after callus formation, the explants cultured on the regeneration medium added with 0–1.75 mg/L 6-benzyladenine (BA). Out of the four cultivars tested, ‘Barvado’ in 7.5 mg/L (51.83 %), and ‘Finelawn Elite’ in 10 mg/L 2,4-D (54.06 %) had better callusing, respectively. However, regeneration percentage was higher in ‘Barlexas II’ (73.15 %) and ‘Finelawn Elite’ (70 %) in 0.5 mg/L BA. Transformation was done in Murashige and Skoog (MS) modified medium by Agrobacterium tumefaciens strain LBA4404 harboring binary vector pCAMBIA 2301. Transgenic calli and plantlets were confirmed by GUS gene expression as non-destructive, non-invasive and useful marker. Maximum rate of callus transformation was shown on modified medium type 11 for ‘Coronado TDH’ and ‘Barlexas II’ (23 % and 22 %, respectively). When the calli samples were placed on the selection media, a high rate of calli (with no successful activity of neomycin phosphotransferase II (NPTII)) had not the ability to regenerate and died. Therefore, the highest rate of regenerated transgenic plantlets containing NPTII and GUS genes (6 %) was belonged to medium type 6 and ‘Coronado TDH’.